Navigating and Combating “Digital Information Minefields” in our Era of Digital Deceit - Black, Joanna; Fullerton, Cody (Advances in Social Sciences Research Journal, 2022)
In our post-truth era, it is becoming increasingly difficult for people to deal with fake news, artificial intelligence, increasing algorithms, Internet censorship, and resulting manipulation of digital users. Social media usage and digital technologies are utilized not only in people’s daily lives, but also in educational contexts. In this perplexing political and corporate landscape, a university Education Librarian and Education Professor working in a Faculty of Education have teamed together to examine ways to address this minefield in their case study research involving ninety-one students. Outlined is a collaborative, responsive, pedagogical approach in which critical research skills and educational curricula are delineated and related to creative and participatory educational practices. An emphasis is placed on arts-based inquiry and student imaginative collaboration. This pedagogy enables students to become more critical consumers and skilled producers of knowledge, facilitating student research and communication of well-developed ideas within their own digital and teaching lives.